Building a training program based on mathematical excellence skills for mathematics teachers and its impact on the achievement of their students - Al-azawy, Osamah; Jasim , Basim (Al-Adab Journal, 2025)
The research aims to build a training program based on mathematical excellence skills for mathematics teachers and its impact on the achievement of their students. The researchers adopted the experimental research method and the experimental design for the control group, with a post-test. In order to verify the research objective, the following null hypothesis was established: "There is no statistically significant difference at a statistical significance level at a significance level of 0.05)) between the average differences in the scores of the students of the experimental group whose teachers underwent the training program based on mathematical excellence skills and the differences in the scores of the students of the control group whose teachers did not undergo training according to the program in the achievement test." The program was built and the experiment was applied to a sample of first-year middle school students for the academic year 2023-2024 whose teachers were selected by random drawing from the research community from those who did not fail in their classes. (10) students were randomly selected for each teacher, so that the total number would be (320) students, The students were divided into two groups, one of which represents the group whose teachers underwent the training program, numbering (160) students, and the other represents the group whose teachers did not undergo the training program, numbering (160) students. The two groups of students were rewarded for the variables (chronological age in months, previous achievement in mathematics, intelligence). The research tool represented by the achievement test was built and its validity, reliability and psychometric properties were verified. The teachers of the experimental group were trained based on mathematical excellence skills. After completing the application of the experiment, the research tool was applied to the students of both groups. The results of the T-test for two independent samples showed that the students of the teachers of the experimental group outperformed the students of the teachers of the control group in the achievement test. In light of the results, the researchers concluded that the experimental program based on mathematical excellence skills had an impact in raising the level of achievement of their students and also contributed to meeting some of the training needs of mathematics teachers.